Intellectual Capital and Performance in Higher Education Organizations - Barbosa, Soraia (2016)
This paper intends to explore the relative importance of different Intellectual Capital (IC) dimensions regarding their contribution to the perceived performance of an Higher Education Organization (HEO). It also seeks to discuss the role of IC and performance measurement in these organizations. This is done through a case study conducted in a Portuguese HEO. The particularities of this type of organization turns it into a very interesting empirical ground for IC research. Evidence suggests that although human, structural and relational capital should contribute as a “whole” to the performance of an HEO, human resources have an added importance as source of knowledge. Results also suggest an ‘overlap’ between IC and performance indicators. Despite the validity of the interpretations provided in the context of the case study, generalization to other situations should only be conducted in a theoretically framed manner. This paper contributes to the development of IC research in a specific type of organization: an HEO. This empirical context is still underexplored, namely regarding the relationship between IC and performance. This study provides important managerial implications for HEOs and their members, who are concerned with its performance and competitiveness.